Yearning for Form and Other Essays on Hermann Cohen's Thought - Poma, Andrea (Studies in German Idealism, 2006)
Hermann Cohen's philosophy has now, finally, received the recognition it deserves. Cohen's thought undoubtedly has all the characteristics of a classic. It faced the great problems of philosophical tradition, with full critical awareness and, at the same time, with the capacity to open up new, original routes. It represents one of the last expressions of great systematic thought. The papers collected in this volume deal with different aspects of Cohen's thought, ethical, political, aesthetic and religious aspects in particular. However, they all represent attempts to follow the ubiquitous presence of certain important themes in Cohen and their capacity for containing meanings that cannot be limited to a single philosophical sphere: themes that are keys to reading unity of inspiration in his thought, which is more deeply imbedded than the exterior architectural unity of his work. The search for the fundamental themes behind Cohen is an important task, if we wish to see this philosopher as a present-day vital point of reference, and not only as a monument of the past.